Poly(dimethyl siloxane)-containing five-block copolymers: Effects of resin blocks - Uyanik, N.; Yalçinkaya, H.; Kizilcan, N. (Springer Science and Business Media LLC, 2001)
A new generation of a series of five-block copolymers from acetophenone-formaldehyde resins (AFR), poly(dimethyl siloxane) (PDMS), and poly(vinyl pyrrolidinone) (PVP) or poly(styrene) (PS) were synthesised to modify the compatibilities and surface properties of the block copolymers. For this purpose, PDMS-AFR-PDMS copolymers, which had different molecular weights and different AFR contents, were prepared first. These three-block copolymers were made diradicalic macroinitiators by a stepwise procedure. Vinyl pyrrolidinone and styrene were polymerised by using these diradicalic macroinitiators to prepare five-block copolymers. Intermediates and copolymers were characterised by physicochemical methods, FTIR and 1 H-NMR spectra. The molecular weights of block copolymers were measured by viscometry and by GPC. The solubility and thermal properties of copolymers and contact angles of block copolymeric films were measured. The overall results indicated that the chain-extended ketonic resins, even in the middle block, affect the characteristics of PDMS containing PVP or PS-block copolymers.